THE EFFECT OF LEADERSHIP STYLES, MANAGERIAL SKILLS AND WORK DISCIPLINE ON THE JOB PERFORMANCE OF PRINCIPALS OF PUBLIC SENIOR HIGH SCHOOLS - Mukmin Jauhari; Bedjo Sujanto; Thamrin Abdullah (Program Pascasarjana Universitas Negeri Jakarta, 2017)
The objective of this research is to study the effect of leadership styles, managerial skills and work discipline on the job performance of principals of public senior high schools in Jakarta Province. This research used the survey method. The samples of this research were 89 persons selected randomly. The data were analyzed by using descriptive statistics and path analysis in inferential statistics. The results of the research concluded that: leadership styles, managerial skills and work discipline had a direct effect on the job performance of principals of senior high schools; leadership styles and managerial skills had a direct effect on principals’ work discipline in public senior high schools, and leadership styles had a direct effect on work discipline of principals of public senior high schools. Therefore, to improve principals’ job performance, leadership styles, managerial skills and work discipline should be improved. Keywords: Leadership Styles, Managerial Skills, Work Discipline, and Job Performance